2012
DOI: 10.1155/2012/285854
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-Mutated Citrullinated Vimentin Antibodies, Anti-Cyclic Citrullinated Peptide Antibodies and Rheumatoid Factor in Omani Patients with Rheumatoid Arthritis

Abstract: Rheumatoid factor (RF) is currently used in the diagnosis of rheumatoid arthritis (RA). The discovery of anticitrullinated protein autoantibodies has led to the development of various new tests, such as anti-cyclic citrullinated peptide (anti-CCP) antibodies, and anti-mutated citrullinated vimentin (anti-MCV) antibodies, to diagnose RA. The aims of this study were to determine the sensitivity and specificity of anti-MCV antibodies in comparison with anti-CCP antibodies and RF in Omani Arab patients with RA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
12
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 18 publications
6
12
2
Order By: Relevance
“…20 On the other hand there were no significant differences in the mean serum levels of RF, Anti-CCP, and Anti-MCV between the early and established cases of RA. This finding disagree with the results of Al-Shukaili et al (2012), who found that both anti-CCP and anti-MCV antibodies are present in very early stages of RA 18 . While, Mathsson et al (2008) reported that in early RA patients anti-MCV yields greater sensitivity and unchanged specificity when compared with the anti-CCP antibodies.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…20 On the other hand there were no significant differences in the mean serum levels of RF, Anti-CCP, and Anti-MCV between the early and established cases of RA. This finding disagree with the results of Al-Shukaili et al (2012), who found that both anti-CCP and anti-MCV antibodies are present in very early stages of RA 18 . While, Mathsson et al (2008) reported that in early RA patients anti-MCV yields greater sensitivity and unchanged specificity when compared with the anti-CCP antibodies.…”
contrasting
confidence: 99%
“…18 Other studies estimated the sensitivity and specificity of the anti-citrullinated peptide antibodies (ACPA) (anti-CCP antibodies, and anti-MCV antibodies) in RA, other autoimmune diseases and in healthy controls reported heterogeneous results. In study made by Nicaise Roland et al (2008), they reported that the specificity of anti-MCV antibody was lower than that of anti-CCP, (90.9%& 94.7%).…”
mentioning
confidence: 99%
“…(15)(16)(17)(18) More in depth analysis within the ACPA results shows that both anti CCP and anti MCV significantly correlated with DAS28 with higher significance towards the anti CCP, Several studies have addressed the diagnostic ability of the MCV assay to be stratified at lower sensitivity and specificity, than the anti CCP. (19,20) . Al-Shukaili and his colleagues in their study also reported anti-CCP antibodies to have a higher sensitivity for the prediction of RA development and activity , in comparison to anti-MCV which come in agreement with our results and indicating that anti CCP may be a better indicator than the anti MCV for detection of disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Shukaili and his colleagues in their study also reported anti-CCP antibodies to have a higher sensitivity for the prediction of RA development and activity , in comparison to anti-MCV which come in agreement with our results and indicating that anti CCP may be a better indicator than the anti MCV for detection of disease activity. (20) . Our study limitation includes lack of use of magnetic resonance imaging (MRI) for actual quantitative assessment of synovial tissue but due to the high expense of MRI in comparison to US, plus the proven evident reliability and efficiency of US were lead us to depend on US.…”
Section: Discussionmentioning
confidence: 99%
“…A previous systematic review revealed a sensitivity of 0.64-0.84 and a specificity of 0.79-0.96 for anti-MCV in the diagnosis of RA [12], but it remains unclear if the overall diagnostic values of anti-MCV antibodies are comparable to anti-CCP antibodies. Published studies on the diagnostic accuracies of anti-MCV and anti-CCP showed controversial results [13,14,15,16,17,18,19,20,21,22,23,24]. This may be due to small sample sizes, low statistical power, and/or clinical heterogeneity.…”
mentioning
confidence: 99%